National Policy for Carbapenem-Resistant Enterobacteriaceae (CRE) Clearance and Discontinuation of Contact Precautions for CRE Carriers in Post–Acute Care Hospitals in Israel: Impact on Isolation-Days and New Acquisitions. (8th February 2020) - Ben-David, Debby; Masarwa, Samira; Fallach, Noga; Temkin, Elizabeth; Solter, Ester; Carmeli, Yehuda; Schwaber, Mitchell J
Abstract: Background: In 2009, the Israeli Ministry of Health implemented in post–acute care hospitals (PACHs) a process of discontinuing carbapenem-resistant Enterobacteriaceae (CRE) carrier status. We evaluated the policy's impact on isolation-days, CRE prevalence among known carriers who had completed clearance testing, and CRE acquisition among noncarriers. Methods: This retrospective study summarized findings from all 15 PACHs in 2009–2017. CRE carriers were considered cleared and removed from contact isolation after 2 rectal cultures negative for CRE and polymerase chain reaction negative for carbapenemases. Data sources included routine surveillance and 4 point prevalence surveys conducted from 2011 to 2017. Results: During the study period, 887 of 6101 CRE carriers (14.5%) completed clearance testing. From 2013 to 2016, the percentage of patient-days in CRE isolation decreased from 9.4% to 3.9% ( P = .008). In all surveys combined, there were 819 known CRE carriers; 411 (50%) had completed clearance testing. Of these, 11.4% (47/411) were CRE positive in the survey. At the ward level, the median percentage of patients with no CRE history who were positive on survey decreased from 11.3% in 2011 to 0% in 2017 ( P < .001). We found no ward-level correlation between the proportion of carriers who completed clearance and new acquisitions (ρ = 0.02, P = .86). Conclusions: A process for discontinuing CRE carrier status in PACHs led to a significant reduction in the percentage of patient-days in contact isolation without increasing CRE acquisitions among noncarriers. Abstract : After implementation of Carbapenem-Resistant Enterobacteriaceae (CRE) clearance testing in post–acute care hospitals, the percentage of patient-days in CRE isolation decreased from 9.4% to 3.9%, with no increase in risk of CRE acquisition among noncarriers.